2016
DOI: 10.1007/s10236-016-0959-6
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the Brazil Current baroclinic structure and variability near 22° S in Distinct Ocean Forecasting and Analysis Systems

Abstract: The Brazil Current (BC) is the Western Boundary Current of the South Atlantic subtropical gyre, the dominant dynamic feature in the South Atlantic Ocean. The importance of this current lies in that it is the main conduit of subtropical waters to higher latitudes in the South Atlantic Ocean. This study assesses the structure and variability of the BC across the nominal latitude of 22°S using data from the high-density eXpendable BathyThermograph (XBT) AX97 transect and from three numerical ocean models with dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 43 publications
3
28
0
1
Order By: Relevance
“…The mean (±1σ) transport of the BC east of 40.9°W is 4.7 ± 1.9 Sv southward, similar to the earlier estimates ranging from 4.4 to 5.3 Sv (Evans et al, ). The transport standard deviation (±1.9 Sv) is approximately half of the mean, showing the strong contribution from eddy variability to the BC (e.g., Lima et al, ; Soutelino et al, ). The shelf contribution, defined here as the region west of 40.9°W and shallower than 300 m, is of 0.9 ± 0.9 Sv, giving a total southward transport of 5.5 ± 1.7 Sv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean (±1σ) transport of the BC east of 40.9°W is 4.7 ± 1.9 Sv southward, similar to the earlier estimates ranging from 4.4 to 5.3 Sv (Evans et al, ). The transport standard deviation (±1.9 Sv) is approximately half of the mean, showing the strong contribution from eddy variability to the BC (e.g., Lima et al, ; Soutelino et al, ). The shelf contribution, defined here as the region west of 40.9°W and shallower than 300 m, is of 0.9 ± 0.9 Sv, giving a total southward transport of 5.5 ± 1.7 Sv.…”
Section: Resultsmentioning
confidence: 99%
“…From the SSHA maps in Figures c and d, it is observed a stationary eddy near 40°W along the XBT transect, generating a trough in sea level of more than 10 cm throughout the 3‐month period. This is the so‐called Sao Tome eddy, a semipermanent cyclonic feature that develops in the region and can be originated from a detachment of a BC meandering (Calado et al, ; Campos et al, ; Lima et al, ). Therefore, our results suggest that in the summer 2009/2010, a mix of positive SSH anomalies propagated westward, anticyclonic wind anomalies facilitating the coastal upwelling and decreasing the coastal sea level, and a stationary eddy near 40°W along the XBT transect contributed for the strong BC anomaly in that period.…”
Section: Resultsmentioning
confidence: 99%
“…Lima et al . [] compared the HYCOM NCODA product with XBT data collected at 22°S between 2004 and 2012. The authors observed that HYCOM NCODA confirmed the transport and variability of the BC in the region.…”
Section: Methodsmentioning
confidence: 99%
“…The NCODA system assimilates available satellite and in situ vertical temperature and salinity profiles of expendable bathythermographs (XBTs), Argo floats, and moored buoys [Cummings, 2005;Cummings and Smedstad, 2013]. Lima et al [2016] compared the HYCOM NCODA product with XBT data collected at 228S between 2004 and 2012. The authors observed that HYCOM NCODA confirmed the transport and variability of the BC in the region.…”
Section: Methodsmentioning
confidence: 99%
“…Studies to tackle the representation of physical systems behavior have been carried out and published in the scientific regionally configured numerical models. In particular, one can indicate the Brazilian REMO project (Lima et. al., 2016), Australian Blue Link project (Schiller et.…”
mentioning
confidence: 99%